Moderating Effect of Firm Characteristics on the Relationship between Electric Power Outage Dynamics and Financial Performance of Manufacturing Firms in Kenya - Njiraini, Winfred Wanjiku; Mwangi, Mirie; Kaijage, Erasmus; Ganesh, Pokhariyal (European Scientific Journal, ESJ, 2021)
Past literatures on the correlational link between electric power outage dynamics and performance of manufacturing firms, in most economies, have portrayed a controversial conceptual debate amongst scholars with little focus on the moderating role played by firm characteristics. This paper focuses on determining the effect of firm characteristics (capital structure) on the relationship between electric power outage dynamics and financial performance of manufacturing firms in Kenya. Positivism philosophical point of view and descriptive survey research design was utilized. A population of 447 manufacturing firms in Kenya, which were also members of Kenya Manufacturers Association, was selected out of which a sample size of 138 firms was drawn using stratified random sampling methodology. Structured questionnaires were utilized to collect data which involved drop and pick approach. The research results indicate that the relationship between electric power outage dynamics and performance of manufacturing firms in Kenya is not significantly moderated by firm characteristics. This study outcome augments existing knowledge on electric power outage dynamics in relation to firm characteristics and financial performance. This is because it is evident that top management should not focus on capital structure as a conditional factor when making decisions aimed at enhancing firm financial performance under power outage conditions. The study has also made an input to the academic literature ascending from empirical reinforcement of tradeoff theory and pecking order theory in making determination on firms’ capital investments. Policy makers and power utilities benefit in understanding the negative effect of power outages on the performance of firms are therefore guided in overseeing the planning and implementation of proper electricity infrastructure. Kenya Association of Manufacturers (KAM) will find these research findings useful in guiding their member firms on strategies to adopt to ensure continuous productivity and safeguard damages to the firm as a result of electric power outages.